The effects of cooperative R and D subsidies and subsidized cooperation on employment growth - Tom Broekel; Antje Schimke; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2011)
The paper investigates the contribution of cooperative and non-cooperative R and D subsidies to firm growth. Of particular interest is hereby firms' embeddedness into subsidized cooperation networks. For the empirical analysis we utilize an unbalanced panel of 2.199 German manufacturing firms covering the time period from 1999 to 2009. A dynamic panel estimation technique is employed to control for growth autocorrelation as well as endogeneity. Our findings show that non-cooperative R and D subsidies have a stimulating impact on large firms' employment growth. In contrast being engaged in many subsidized cooperation is related to significant growth-reducing effects. In the case of large firms, exceptions are subsidized cooperation with geographically distant firms, which can positively influence employment growth. For small firms, rather interactions with research organizations are found to facilitate their development.
Keywords: H25; J23; D85; 330; R and D subsidies; cooperation network; firm growth; serial correlation